On the meaning of ribā [interest] and its effect on the Nigerian economy (2017)
The role of financial intermediation in a modern capitalist system hinges mainly on the taking and charging interest. While some Islamic scholars consider interest to be lawful for Muslims to take or charge on their transactions, many Islamic scholars consider charging or taking interest to be non-shari’ah compliant. It is against this backdrop that the paper sets out to provide a correct articulation of the meaning of ribā [interest/usury], which is the foundation stone on which the conventional financial institutions are based and examines its effects on the Nigerian economy. Using information about the forms and structure of socio-economic transactions during al-Jahiliyyah (pre-Islamic) period in Makkah and during the Prophet’s time in Makkah and Madinah, we found that interest of all kinds is prohibited. The practice of interest payment in a modern capitalist economy is against the dictates of the Shari’ah. The article finds that debt servicing has badly affected the economic growth development of Nigeria. The article reveals a sharp increase in the amounts used to finance the country’s debt obligation. The debt servicing as a percentage of the capital expenditure has been increasing greatly since 2011 to till date. The percentage of debt servicing to capital expenditure in Nigeria from 1981 to 2015 has been very high for the country, with an average of over 59.0% under the 35 years considered in this study. In some years, this ratio was over 100.0% reaching its peak at 150.4% in 2003. In 2015, the ratio stood at 129.57%. This could account for low level of development in the country. The negative impact of debt servicing on the economy serves as a barrier to poverty alleviation, economic growth and development.